ASSA13-01-10 Value of BNP, WBC, Creatinine, TNT and CK-MB to Predict Acute Myocardial Infarction Mortality During Hospitalisation in Patients Aged 80 and Over. (29th April 2013) - Jing-guang, Luo; Ming, Yang; Ling, Han; Li-wei, Chen; Kang, Gao; Yan, Zhao; Hai-feng, Liang; Xin, Chen
Abstract : Objective: To detect the value of B-type natriuretic peptide (BNP), white blood count (WBC), Creatinine, TNT and CK-MB in predicting acute myocardial infarction (AMI) mortality in patients aged 80 and over. Methods: Mortality is defined as all-cause death rate during hospitalisation. The discrimination ( c statistic) was evaluated. Results: 384 patients presenting with ST segment elevation AMI (STEMI) and non-STEMI were enrolled. The mortality was 23.4%. The overall discriminatory capacity of BNP, WBC, Creatinine, TNT and CK-MB was 0.755 (95%CI: 0.7–0.811), 0.658 (95%CI: 0.593–0.723), 0.647 (95%CI: 0.578–0.716), 0.626 (95%CI: 0.562–0.690) and 0.619 (95%CI: 0.558–0.679), respectively. The discriminatory capacity of the BNP was good. Conclusions: BNP is a useful risk predictor for hospital mortality of AMI patients aged 80 and over.